EUCALYPTUS SPP. GLUED LAMINATED TIMBER WITH REINFORCED FIBER FINGER-JOINTS - Bourscheid, Cleide Beatriz; Terezo, Rodrigo Figueiredo (Floresta, 2020)
Reinforcement for flexion in structural elements with finger-joints using fibers has emerged as a particularly suitable technique for timber. Thus, the objective of this study was to evaluate the performance of Glued Laminated Timber (GLULAM) produced with Eucalyptus spp. wood and three reinforcement compositions, “Glass”, “Glass2” and “Carbon” regarding parallel-to-grain tensile strength, normal tensile strength, shear strength and the three-point bending test. All the tests were performed according to the NBR 7190/1997 using the Tukey test for statistical analyzes and a 95% confidence interval. The performance of the Eucalyptus spp. GLULAM did not present significant differences in evaluation of the bonding lines. However, the “Glass 2” and “Carbon” treatments were significantly superior to the GLULAM samples without reinforcement in bending strength, reaching increments of 37.8% and 40.5%, respectively. The modulus of elasticity did not differ significantly between them. A tensile rupture was observed in the region of the finger-joints in all the evaluated samples; however, the flexural tensions were superior to the parallel-to-grain tensile strengths, indicating an influence of the timber thickness and reinforcement thickness on the performance of the reinforced joints. Thus, it is possible to conclude that applying concentrated reinforcement in the region of the finger-joints significantly improves the performance of Eucalyptus spp. GLULAM samples.